Principles of population studies - Bhende, Asha.A.; Kanitkar, Tara (Bombay, 1978)
The present work is perhaps the only book on population studies which is mainly based on Indian data and meant for Indian students. It will therefore be found to be useful to students and teachers alike, both at the undergraduate and post graduate levels. Even research scholars, we hope, will find it useful as an introduction to the subject, while the general reader will find much of interest in this book because it explains population processes in simple terms, after defining the various concepts.
Keywords: Population policy